Bis(isobutyl-ammonium) phthalate monohydrate. - Norzalida, Z.; Ariffin, A.; Ng, Seik Weng (International Union of Crystallography, 2008)
N-Isobutyl-phthalimic acid hydrolyzes to the title salt, 2C(4)H(12)N(+)·C(8)H(4)O(4) (-)·H(2)O, which adopts a hydrogen-bonded layer structure. In the anion, the carboxyl-ate groups are twisted with respect to the benzene ring [dihedral angles = 43.8 (1) and 50.9 (1)°].